Dosimetric platform and a genuine Raman protocol for passive estimation of fast-neutron fluence in irradiated SiC and SiC topped with epitaxial graphene - Jakub Jagiełło; Artur Dobrowolski; Tymoteusz Ciuk; Rafał Prokopowicz; Barbara Bieńkowska; Jakub Włodarczyk; Semir El-Ahmar; Maciej J. Szary; Mirosław Szybowicz (Results in Physics, 2025)
The article introduces a genuine ex-situ measurement protocol to estimate the integrated flux of mostly fast (1-2 MeV) neutrons. It is verified up to the fluence of 6.5 × 1018 n/cm2. A dedicated dosimetric platform comprises p-type hydrogen-intercalated quasi-free-standing epitaxial Chemical Vapor Deposition graphene on semi-insulating vanadium-compensated nominally on-axis 6H-SiC(0001) and a 100-nm-thick atomic-layer-deposited amorphous aluminum oxide encapsulation. The methodology correlates the total area under the averaged Raman spectra of SiC, between 60 cm-1 and 1200 cm-1, upon prior normalization to the maximum value of the longitudinal optical mode at 964 cm-1. The patterned a-Al2O3/QFS-graphene/6H-SiC(0001) system offers two verification mechanisms — one within the graphene mesa and the other outside. Following the protocol, one can read the neutron fingerprint in the material and relate it to the integrated flux. The passive character of the method eliminates the radiological hazards associated with traditional activation methods. The approach enables localized and precise fluence control in fissile and thermonuclear facilities with a Root Mean Squared Percentage Error of the fitted model of approximately 4%.